Relações evolutivas e história demográfica em espécies de Harttia Steindachner, 1876 - Sassi, Francisco de Menezes Cavalcante (2025)
This thesis explores the evolutionary, cytogenomic, and filogeographic relationships of the genus Harttia, a genus of fish widely distributed across Brazil. Due to its diversity of sex chromosome systems, including simple (XX/XY) and multiple (XX/XY1Y2 and X1X1X2X2/X1X2Y) systems found in approximately 28% of cytogenetically investigated species, Harttia stands out as one of the few natural repositories of multiple sex chromosomes, offering unique insights into chromosomal evolution. We generated novel data for six species (H. dissidens, H. duriventris, H. guianensis, H. rondoni, H. villasboas and Harttia sp. 3), integrating cytogenetic, genomic and phylogeographic methodologies. The thesis pioneered the proposal of a phylogeny for the genus using genome-wide data (DArTseq SNPs), enhancing perspectives on evolutionary relationships by characterizing the three major clades associated with different biogeographic regions: one composed of species from the Guiana Shield (Clade I), another by species from the drainages of Northern Brazil (Clade II), and the third by species from Southern and Southeastern Brazil (Clade III). Biogeographic modeling suggests that the genus’ ancestor inhabited the Amazon, Paraná, or South Atlantic coastal basins, with secondary colonization into the Tocantins-Araguaia, São Francisco, and East Atlantic basins. Cytogenetic analyses (mapping of repetitive DNAs by FISH, comparative genomic hybridization - CGH, and whole chromosome painting - WCP) revealed that half of the species studied here have distinguishable sex chromosomes, including new occurrences of the X1X2Y multiple system and the first occurrence of XX/XY in a clade II species. The chromosome number evolution modeling data and sex linked markers suggests that these systems derive from an ancestor with a 2n = 58 karyotype and XX/XY system, sharing sex-linked markers among species of clades I and III, and suggesting a turnover event in clade II. Additionally, sex-linked markers indicate that all 16 investigated species exhibit a male heterogametic sex chromosome system (eight previously known for their cytogenetic heteromorphism), suggesting the presence of simple homomorphic systems (XX/XY) in eight species (H. dissidens, H. guianensis, Harttia sp. 3, H. kronei, H. longipinna, H. loricariformis, H. gracilis, and H. fowleri). Furthermore, while the fusion of sex chromosomes with autosomes enabled the emergence of multiple sex systems in clade III, chromosome painting data show that chromosome fissions were crucial for the differentiation of sex chromosomes in clade II. Chromosomal differentiation, investigated through repetitive DNAs (satellites, microsatellites, ribosomal DNAs), suggests that geographic isolation and historical factors shaped the genetic structure and evolutionary divergence within the genus. In conclusion, this work contributes significantly to understanding the cytogenomics and demographic evolution of Harttia, establishing it as a valuable model for exploring diversification in Neotropical environments.